Analisis Strategi Pembelajaran di SDN Cibanjaran - Sunanih Sunanih; Novi Nurhopipah; Zulia Latifah; Hilda Nurhidayah; Neng Hilma Paujiah; Fiani Septi Mutmainah; Rismawati Nurapipah; Salma Maulida Iskandar; Asti Rahmawati; Sophie Novia; Alin Nurliana; Alivia Nuruliva; Yuli Anggraeni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to identify and evaluate learning strategies at SDN Cibanjaran. Using a descriptive qualitative approach, the study relied on in-depth interviews, observations and group discussions to explore criticisms and suggestions for learning methods. The findings show that effective learning strategies involve a differentiated approach, where materials and methods are tailored to students’ individual needs. Problem-based learning (PBL) and project-based learning (PJBL) models are considered to increase student relevance and motivation. However, the different characteristics of today’s students compared to those of the past pose new challenges, especially in the application of discipline, which must now be more humane. In addition, adjusting to the Merdeka Curriculum is crucial, where teachers are encouraged to continue learning through platforms such as PMM. This study concludes that learning strategies need to adapt to changing times, environments and student needs to create a meaningful learning process. The implications of this study emphasize the importance of inclusive and dynamic learning, and the role of teachers as innovative facilitators.